Solid mechanics simulation of reconstructed gas diffusion layers for PEMFCs - Xiao, Liusheng; Luo, Maji; Zhang, Heng; Zeis, Roswitha; Sui, Pang Chieh (Journal of The Electrochemical Society, 2019)
This paper reports on the development of a novel approach to investigate the stress and strain distributions at the fiber's scale of PEMFC gas diffusion layers (GDLs). The present method includes stochastic reconstruction and finite element solution procedure. The microstructure of a GDL was randomly generated and meshed, upon which solid mechanics simulations were performed. Stress and strain distributions in three dimensions were obtained by considering dynamic contact, frictional motion and extruding deformation of the fibers. A sensitivity analysis on the present model showed that frictional coefficient between fibers has more influence on the model results than the mechanical properties of the fiber. Our simulation results show that under compression, the fiber's displacement in the through-plane direction is significantly more than the in-plane direction. Fibers intruding into the gas channel were also observed. For the case with 20% compression ratio, the computed stress is mostly below 100 kPa with a maximum in excess of 1,000 kPa. Simulation results, which include stress and displacement distributions under compression, are in qualitative agreement with actual observations in the literature. The present methodology can be extended to most porous electrodes that involve material deformation to allow accurate evaluation of their transport properties and performance.
CRIS-Team Scopus Importer:2023-08-01